The innovation diffusion, technology adoption, and digital etnopedagogical reading: English lecturer’s agency in reinforcing the ability of the younger generation to retain local knowledge - Marzulina, Lenny; Sofendi; Mirizon, Soni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
This study examines the role of English lecturers as change agents in promoting innovative digital ethnopedagogical reading in higher education settings. Even though higher education in Indonesia is becoming increasingly digitally oriented, technology adoption is often tool-centered rather than culturally aware, potentially endangering the ability of younger generations to retain local knowledge. This research investigates the factors that influence innovation diffusion and investigates the integration of digital tools with local cultural values (Bidar, Pulau Kemaro, Rumah Limas, Songket Palembang, Kue Maksuba) in reading instruction, as mediated by a lecturer at a state university in Palembang, South Sumatra. Data were gathered from six students chosen through purposive sampling and one lecturer, using a qualitative intrinsic case study design, until data saturation was reached. Primary data collection instruments included semi-structured interviews (lasting 20-30 minutes via WhatsApp video calls) and document analysis (YouTube videos, reading scripts, and chat logs). Four primary themes were identified through thematic analysis in accordance with (Braun & Clarke, 2006): the dynamics of drivers and barriers in innovation diffusion, the transformative impact on linguistic competence and cultural awareness, the systematic implementation through digital platforms, and the dual motivation (pragmatic efficiency and cultural preservation). The results indicate that culturally responsible lecturers, rather than institutional mandates, are the primary driving force behind sustainable innovation. By combining their cultural pride with their English language skills, students created a